Peri‐operative continuation of metformin does not improve glycaemic control in patients with type 2 diabetes: A randomized controlled trial. Issue 3 (13th October 2017) - Hulst, A. H.; Polderman, J. A. W.; Ouweneel, E.; Pijl, A. J.; Hollmann, M. W.; DeVries, J. H.; Preckel, B.; Hermanides, J.
Abstract : Historically, metformin was withheld before surgery for fear of metformin‐associated lactic acidosis. Currently, however, this risk is deemed to be low and guidelines have moved towards the continuation of metformin. We hypothesized that continuing metformin peri‐operatively would lower postoperative serum glucose level without an effect on plasma lactate levels. We performed a single‐blind multicentre randomized controlled trial in people with type 2 diabetes mellitus scheduled for non‐cardiac surgery and continued (MF+ group) or withheld (MF‐ group) metformin before surgery. The main outcome measures were the differences in peri‐operative plasma glucose and lactate levels. We randomized 70 patients (37 MF+ group and 33 MF‐ group) with type 2 diabetes mellitus. Postoperative glucose levels were similar in the MF+ and the MF‐ groups (8.2 ± 1.8 vs 8.3 ± 2.3 mmol/L P  = .95) Although preoperative lactate levels were slightly higher in the MF+ group compared with the MF‐ group (1.5 vs 1.2 mmol/L; P  = .02), the postoperative lactate levels were not significantly different (1.2 vs 1.0 mmol/L; P  = .18). In conclusion, continuation of metformin during elective non‐cardiac surgery does not improve glucose control or raise lactate levels to a clinically relevant degree.